2016
DOI: 10.5751/es-08747-210420
|View full text |Cite
|
Sign up to set email alerts
|

Ancient clam gardens, traditional management portfolios, and the resilience of coupled human-ocean systems

Abstract: ABSTRACT. Indigenous communities have actively managed their environments for millennia using a diversity of resource use and conservation strategies. Clam gardens, ancient rock-walled intertidal beach terraces, represent one example of an early mariculture technology that may have been used to improve food security and confer resilience to coupled human-ocean systems. We surveyed a coastal landscape for evidence of past resource use and management to gain insight into ancient resource stewardship practices on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 28 publications
3
49
0
Order By: Relevance
“…Moreover, transplant experiments showed that juvenile little neck clams grew 1.7 times faster and were more likely to survive in clam gardens than non-walled beaches (Groesbeck et al 2014). Similarly, recent research on British Columbia's Central Coast, 250 km north of Quadra Island, revealed that clam gardens encompassed twice the biomass and density of butter clams than unmodified beaches (Jackley et al 2015). In both cases, we found that differences in clam biomass between the two beach types were most pronounced at the upper tidal elevation of ideal clam habitat.…”
Section: Clam Garden Morphology and Ecologysupporting
confidence: 76%
“…Moreover, transplant experiments showed that juvenile little neck clams grew 1.7 times faster and were more likely to survive in clam gardens than non-walled beaches (Groesbeck et al 2014). Similarly, recent research on British Columbia's Central Coast, 250 km north of Quadra Island, revealed that clam gardens encompassed twice the biomass and density of butter clams than unmodified beaches (Jackley et al 2015). In both cases, we found that differences in clam biomass between the two beach types were most pronounced at the upper tidal elevation of ideal clam habitat.…”
Section: Clam Garden Morphology and Ecologysupporting
confidence: 76%
“…Walker et al (2006) argued over a decade ago that "some regimes that are considered undesirable can also be very resilient, e.g., harsh dictatorships and desertified regions of the Sahel, " and static lock-ins and traps have been identified (Cinner, 2011;Olsson et al, 2014). Nonetheless, the debate on resilience dynamics has remained oddly one-sided, focusing almost exclusively on enhancing sustainability-supporting forms of resilience (e.g., Davidson-Hunt and Berkes, 2002, p. 77;Cutter et al, 2008;Barnosky et al, 2012;Jackley et al, 2016). That this entails the danger of depoliticizing our understanding and decision-making relating to human-nature dynamics has been pointed out recently (Olsson et al, 2015).…”
mentioning
confidence: 99%
“…To ensure a consistent, easily-accessible supply of shellfish, some coastal communities engineered extensive clam gardens near habitation sites ( Fig. 2i, Lepofsky et al 2015, Jackley et al 2016. Constructed by building rock walls in the mid to low intertidal, clam gardens increase sedimentation rates by at least four-fold, which alters the beach slope at tidal heights optimal for clam production (Groesbeck et al 2014, Deur et al 2015, Neudorf et al 2017).…”
Section: Coastal Humansmentioning
confidence: 99%